Additive manufacturing of advanced ceramics by digital light processing: equipment, slurry, and 3D printing - Camargo, Ítalo Leite de (2022)
Additive manufacturing (AM) or 3D printing is a set of technologies that fabricate parts by successively adding layers. This technique is already applied in all classes of materials. In ceramic manufacturing, AM allows the fabrication of small series components with greater geometric freedom, lower cost, and reduced delivery time. Among the AM technologies, vat photopolymerization (VP) stands out for its ability to produce ceramic pieces with excellent dimensional accuracy and surface finish. However, there is a shortage of VP commercial equipment dedicated to producing ceramics at an affordable price, given the challenges of dealing with raw material with high particle loading. In this work, which approaches the fabrication of advanced ceramics by digital light processing VP, the feasibility of using a top- down 3D printer prototype and an ordinary commercial bottom-up printer (usually applied in polymer 3D printing) in the processing of ceramic materials was tested. For this, a 3D printer prototype was designed and built, creating an innovative recoating system (patent pending), composed of two blades with distinct and sequential functions. This system aims to overcome the challenge of creating layers for ceramic suspensions, which usually have high viscosity. In addition, photosensitive suspensions were developed seeking to meet process requirements related to high ceramic loading, rheological behavior, photosensitive parameters, and stability. The ceramic powders were selected to evaluate the process using distinct groups of advanced ceramics: nanometric powders (3Y-TZP) and submicrometric powders (electrofused mullite). Furthermore, a combination of natural raw material (zircon) with alumina was used to investigate the in-situ formation of mullite-zirconia composites in 3D printed parts. Thus, photosensitive ceramic suspensions based on a nanometric zirconia powder (3Y-TZP) were developed and characterized, selecting the appropriate components (monomer, photoinitiator, and dispersant). In this way, a ceramic slurry was obtained capable of validating the developed prototype and manufacturing green ceramic bodies. Nonetheless, the same formulation was not suitable for the commercial 3D printer, due to its rheological behavior not being compatible with the equipment. On the other hand, the submicrometric mullite powder allowed the preparation of formulations with high solid loading (up to 50 vol%). These new formulations were successfully used in both pieces of equipment tested. Furthermore, the formulation based on the mixture of ceramic powders (zircon and alumina) showed that the technique can be combined with reactive sintering to create in-situ mullite and zirconia composites. After analysis of the thermal decomposition, a protocol for the thermal treatment was created and the printed bodies were submitted to burning of the organic components and sintering. Both 3D printers tested proved capable of creating dense ceramic pieces (>95%) and with geometries that would be unfeasible or even impossible by other manufacturing methods. The various characterizations of the sintered bodies (mechanical strength, microstructure, etc.) indicate that there are still limitations when the present route is compared with conventional manufacturing processes. Finally, it is believed that the present study contributes to the knowledge related to the additive manufacturing of ceramics and stands out for presenting an approach accessible to laboratories and small manufacturers of ceramic products.